Pengaruh Kompensasi, Fasilitas Kerja Dan Kemampuan Kerja Terhadap Kinerja Karyawan Pt. Kharisma Jaya Lombok Di Kabupaten Lombok Tengah - Ni Putu Widiantari; Baiq Ertin Helmida; I Nengah Arsana (Kredibel: Jurnal Ilmiah Manajemen, 2024)
The purpose of this study is to examine several things, namely: (1) the effect of compensation on employee performance, (2) the effect of work facilities on employee performance, (3) work ability on employee performance, (4) the effect of compensation, work facilities, and work ability on employee performance. In this study using the type of associative research with a sample of 36 people who are employees of PT. Kharisma Jaya Lombok. The data collection technique in this study is in the form of statements in the form of questionnaires. The results of this study show that: (1) compensation has a significant effect on employee performance. (2) Work facilities have a significant effect on employee performance. (3) Work ability does not have a significant effect on employee performance. (4) compensation, work facilities and work ability have a significant effect on employee performance because the calculated F value is greater than the F table.